Investigation on Interfacial Charge Transfer Process in CdSexTe1-x Alloyed Quantum Dot Sensitized Solar Cells. (10th August 2015) - Wei, Huiyun; Wang, Guoshuai; Luo, Yanhong; Li, Dongmei; Meng, Qingbo
Abstract: Colloidal QDs, typically, alloyed QDs with extending light absorption range, exhibit prospective application on quantum dot-sensitized solar cells (QDSCs). In this work, CdSe0.8 Te0.2 alloyed QDs have been employed to assemble QDSCs, and the influence of the photoanode structure and film thickness on the cell performance has been investigated in detail. Further study on the charge transport and interfacial electron transfer processes reveals that with the film thickness increasing, recombination possibility will be remarkably enhanced. By careful control on the balance between the light absorption and carrier recombination, an optimal double-layer photoanode structure with 11.5 μm-thickness transparent and 6 μm-thickness scattering layers can present a power conversion efficiency of 7.55%, which is one of the best records for the sandwiched-type QDSCs.